The shadow king - Stevenson, Jane 1959- (Houghton Mifflin, 2003)
Balthasar Stuart, the son of Elizabeth of Bohemia and an African prince, works as a doctor in late seventeenth-century Holland, until he is driven out by the plague to build a new life in Restoration London and Barbados.
Sequel to: The winter queen. -- Originally published: London : Jonathan Cape, 2002.
Keywords: Behn, Aphra <1640-1689> -- Fiction; Elizabeth <Queen, consort of Frederick I, King of Bohemia, 1596-1662> -- Family -- Fiction; Geschichte 1600-1700; Geschichte; Physicians -- Fiction; Racially mixed people -- Fiction; Niederlande; Barbados -- Fiction; London (England) -- History -- 17th century -- Fiction; Netherlands -- History -- 1648-1714 -- Fiction; Historical fiction